The Seven Time Managing Strategies of English Teachers to Adapt with the Change in Curriculum - Martaliana, Lidhya; Syahrul, Syahrul; Safitri, Loli (Universitas Lancang Kuning, 2021)
The Indonesian school system curriculum was changed from KTSP to curriculum 2013 (K13) since the year 2013. This alteration of the curriculum dealt an impact by changing the allocated time for English classes. Within KTSP, Teachers taught English subject for four hours session per week, which means four times 45 minutes each week, whereas, within the K13, the allocated time for English subject is a two hours session per week which means two times 45 minutes which means there is a reduction in time for English subject. This study aims to determine how English teachers manage their time by conducting interviews, observations, and documentation analysis on 11th grade English teachers at MAN 1 Pasaman, Indonesia. Findings revealed seven strategies, namely following the school calendar, setting goals and working on achieving those goals, prioritizing the more important goal, making a daily schedule of classroom activities, making a to-do list, setting a time limit for the task in the classroom, and utilising transition time effectively. The findings are a novelty because few studies have identified the specific strategies that English teachers used to successfully adapt to the curriculum change. Thus, this study contributes to future educators preparing and anticipating possible curriculum changes that may drastically change teaching time.